Estimation of dihydroartemisinin in human plasma using a highly sensitive LTQ Orbitrap mass spectrometer with Xcalibur software - Abu-Izneid, Tareq; Abbas, Muhammad; Watson, David G.; Shah, Yasar; Shah, Sayyed I.; Khuda, Fazli (Frontiers in Pharmacology, 2023)
Background: Artemether (ARM), the O-methyl ether prodrug of dihydroartemisinin (DHA), is considered a first-line antimalarial agent. Artemether is extensively metabolized in vivo to its active metabolite DHA, and therefore its determination offers considerable difficulties. In the present study, DHA identification and estimation were accurately performed by the mass spectrometric analysis, using a high-resolution liquid chromatography/electrospray ionization-mass spectrometry (LC/ESI-MS) LTQ Orbitrap hybrid mass spectrometer. Methods: The plasma samples were taken from healthy volunteers, and the spiked plasma was extracted by adding 1 mL of a mixture of dichloromethane and tert.-methyl butyl ether (8:2 v/v) to 0.5 mL of plasma. The internal standard solution (artemisinin 500 ng/mL) was added to the plasma samples. After vertexing and centrifugation, the organic layer was separated and transferred into another tube and dried under nitrogen. The residue was reconstituted in 100 μL of acetonitrile and was injected onto the LC-MS system for analysis. Measurement of standards and samples was carried out isocratically on a Surveyor HPLC system combined with an LTQ Orbitrap mass spectrometer using an ACE 5 C18-PFP column. Mobile phase A consisted of 0.1% v/v formic acid in water, Mobile phase B consisted of acetonitrile only, and isocratic elution was carried out with A:B 20:80, v/v. The flow rate was 500 μL/min. The ESI interface was operated in a positive ion mode with a spray voltage of 4.5 kV. Results: Artemether is not a very biologically stable compound and is immediately metabolized to its active metabolite dihydroartemisinin, so no clear peak was observed for artemether. Both artemether and DHA after ionization undergo neutral losses of methanol and water, respectively, in the source of the mass spectrometer. The ions observed were (MH-H2O) m/z 267.15 for DHA and (MH-m/z 283.15 for internal standard artemisinin. The method was validated according to international guidelines. Discussion: The validated method was applied successfully for the determination and quantification of DHA in plasma samples. This method works well for the extraction of drugs, and the Orbitrap system with the help of Xcalibur software accurately and precisely determines the concentration of DHA in spiked as well as volunteer’s plasma.